Emerging advances in cancer nanotheranostics with graphene nanocomposites: opportunities and challenges. (August 2015) - Rahman, Mahfoozur; Akhter, Sohail; Ahmad, Mohammad Zaki; Ahmad, Javed; Addo, Richard T; Ahmad, Farhan Jalees; Pichon, Chantal
As an inorganic nanomaterial, graphene nanocomposites have gained much attention in cancer nanotechnology compared with the other inorganic nanomaterial in recent times. Although a relatively new drug carrier, it has been extensively explored as a potential chemotherapeutic carrier and theranostic because of its numerous physicochemical properties, including, capability of multiple pay load, functionalization for drug targeting and photothermal effect. Despite potential benefit, its translation from bench to bed-side in cancer therapy is challenged due to its toxicity concern. Here, we discussed the present progress and future possibilities of graphene nanocomposites as a cancer theranostic. Moreover, the paper also exemplifies the effects of graphene/graphene oxide on tissues and organ functions in order to understand the extent and mechanism of toxicity.